1953
DOI: 10.2136/sssaj1953.03615995001700020008x
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Soil Organic Matter from Wood Chips

Abstract: A study was made in cylinders to measure the effect of incorporating 10 tons of pine and oak chips per acre to a Merrimac sandy loam. The influence of such factors as level of nitrate nitrogen, soil reaction, and size of wood chips, were investigated.Using nitrate nitrogen depression as a measure of rate of decomposition, it was found that oak chips decomposed more rapidly than pine chips. This was supported by annual sieving experiments. These measurements showed significantly less oak chips remaining at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Wood and wood co‐composts have long been used as soil amendments in both field and greenhouse applications (King, 1979; Martin et al, 1978; Salomon, 1953; Schuman and Belden, 1991; N'Dayegamiye and Angers, 1993; Tremblay and Beauchamp, 1998). Similar to the composting process of most organic residues, the phytotoxic effects of wood and bark wastes in the composting process are transient (Hardy and Sivasithamparam, 1989; Martin et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Wood and wood co‐composts have long been used as soil amendments in both field and greenhouse applications (King, 1979; Martin et al, 1978; Salomon, 1953; Schuman and Belden, 1991; N'Dayegamiye and Angers, 1993; Tremblay and Beauchamp, 1998). Similar to the composting process of most organic residues, the phytotoxic effects of wood and bark wastes in the composting process are transient (Hardy and Sivasithamparam, 1989; Martin et al, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…even denitrification if NO 3 -N levels in the soils are sufficiently high (Salomon 1953;Allison et al 1963), thereby limiting the availability of compost organic N to plants in the short term. Composts did not act as a slow-release N source for annual row crops, or for annual or perennial nursery crops (Kuo et al 1997;Hummel et al 2000).…”
Section: Finfish Wastementioning
confidence: 99%
“…Applications of N must be made to soil where wood chips have been incorporated to prevent a reduction in plant growth due to N immobilization as the wood chips decompose (Salomon, 1953). Bollen and Glennie (1963) and Schrock and Rothenberger (1997) reported that the addition of N to bark and wood byproducts resulted in increased plant growth due to the reduction of N immobilization.…”
mentioning
confidence: 99%